Experience of Pregnant Mothers in Receiving Ante Natal Care Services in Hospital - Suryani Hartati; Ening Wahyuni (Universitas Malahayati Lampung, 2023)
ABSTRACT Antenatal care services for pregnant women are health services received by mothers during pregnancy to determine the health condition of the mother and fetus. To determine the experience of pregnant women in receiving services at the hospital. This research method is qualitative phenomenology, data collection is carried out in natural settings with participant observation techniques and in-depth interviews. Data were analyzed with the Colaizzi method. Among mothers as hospital visitors, 3 themes were found, namely 1) Utilization of technology in antenatal care services for pregnant women in hospitals, 2) Effective communication with pregnant women as customers in hospitals, 3) Educational literacy for mothers pregnant antenatal care in health services in hospitals. Among health workers as stewards of antenatal care, two themes were found, namely: 1) the use of technology as a means of educational media, and 2) the expectations of health workers in providing services for pregnant women. The use of technology in the form of educational facilities is very important for pregnant women, especially during the antenatal care period, this is useful to help reduce the incidence of complications in the mother and fetus based on health technology monitoring. The involvement of health workers including doctors, nurses, and midwives is a determining factor for success in service excellence in 5 standard policies, namely police, place, product, process, and people in the hospital.